Zindiq Al-Walīd bin Yazīd An Analysis of Orthodoxy and Heterodoxy in the perspective of Civil Society in the Umayyad Dynasty - Akbar, Raabiul; Burhanuddin, Burhanuddin (Program Pascasarjana UIN Sumatera Utara, 2024)
This study takes the case of Zindiq Al-Walīd bin Yazīd as a central point, viewing it as a more political phenomenon with a solid religious background than a purely spiritual issue. This research shows that during the Umayyad Dynasty, the treatment of the Zindiq varied depending on their political impact on the caliph's power. Zindiq, who did not threaten the stability of the ruler, was not punished and even received preferential treatment as heir to the throne. On the other hand, those deemed to interfere with power with political criticism and ties to political rivals were punished. This research uses a qualitative approach using the book Tārkīh al-Ṭabarī Tārīkh al-Rusul wa al-Mulūk by Ibn Jarīr al-Ṭabarī as primary data. A socio-anthropological approach strengthened by Weber's conflict theory was chosen to understand the historical context related to the concepts of orthodoxy and heterodoxy. This research proves a shift in the political context in the zindiq case. This research contributes to a broader understanding of the relationship between authorities and civil society in religious and political contexts.Studi ini mengambil kasus Zindiq Al-Walīd bin Yazīd sebagai titik pusat, memandangnya sebagai sebuah fenomena yang lebih bersifat politis dengan latar agama yang kuat daripada masalah agama murni. Penelitian ini menunjukkan bahwa pada masa Dinasti Bani Umayah, perlakuan terhadap Zindiq bervariasi tergantung pada dampak politik mereka terhadap kekuasaan khalifah. Zindiq yang tidak mengancam kestabilan penguasa tidak dihukum, bahkan mendapat perlakuan istimewa sebagai ahli waris tahta. Di sisi lain, mereka yang dianggap mengganggu kekuasaan dengan kritik politik dan hubungan dengan pesaing politik dihukum. Penelitian ini menggunakan pendekatan kualitatif dengan menggunakan kitab Tārkīh al-Ṭabarī Tārīkh al-Rusul wa al-Mulūk karya Ibn Jarīr al-Ṭabarī sebagai data primer. Pendekatan sosio-antropologi yang diperkuat oleh teori konflik Weber dipilih untuk memahami konteks historis terkait dengan konsep ortodoksi dan heterodoksi. Penelitian ini membuktikan adanya pergeseran konteks politik dalam kasus zindiq. Penelitian ini memberikan kontribusi terhadap pemahaman lebih luas tentang hubungan antara penguasa dan civil society dalam konteks keagamaan dan politik.